2017
DOI: 10.1021/acs.iecr.7b00572
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Sorption of Propane and 1-Hexene in Polyethylene: Experiments and Perturbed-Chain Statistical Associating Fluid Theory Simulations

Abstract: The availability of sorption equilibrium data is important for the design and optimization of polymerization processes. In this work, we used a gravimetric apparatus based on a magnetic suspension balance and the perturbed-chain statistical associating fluid theory (PC-SAFT) equation of state to study the equilibrium sorption of propane and 1-hexene in polyethylene (PE). Propane is used as a diluent in the gas-phase catalytic polymerization of ethylene, while 1-hexene is a commonly used comonomer. Experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Over the last decade, different experimental methods have been developed to measure the solubility of gases in polymers. However, most of these experimental solubility studies are restricted to binary systems (penetrant -PE), with a limited number looking at ternary systems (penetrant 1penetrant 2 -PE) [11][12][13][14][15][16][17][18][19][20] . These studies showed that the solubility of a given component in a polymer is function of the structure of the penetrant, the temperature, the pressure and the polymer density and crystallinity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, different experimental methods have been developed to measure the solubility of gases in polymers. However, most of these experimental solubility studies are restricted to binary systems (penetrant -PE), with a limited number looking at ternary systems (penetrant 1penetrant 2 -PE) [11][12][13][14][15][16][17][18][19][20] . These studies showed that the solubility of a given component in a polymer is function of the structure of the penetrant, the temperature, the pressure and the polymer density and crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors showed the same effect in the presence of co-monomers in ternary systems 13,22,23 . Chmelar et al 14 showed that the sorption of 1-hexene increases ethylene solubility in the amorphous PE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that lighter compounds decrease the solubility of heavier ones, e.g., ethylene is actually an anti-solvent for the ICAs and α-olefins used in this study, so we could expect that a compound like ethane would be as well. [3,10,11] However, no studies have really concentrated on the impact of more than two absorbing species on the actual rate of copolymerization and the impact of this on polymer properties. In the following sections we will look at the impact of different types of ICA (heavier or lighter than the comonomers) on the rates of homo-and copolymerization of ethylene with either 1-butene or 1-hexene, and on the final polymer properties of the polymer produced in the different experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Some groups have looked at the impact of mixtures of species on their mutual solubility in polyethylene (PE) in the absence of polymerization and shown that heavier compounds, like ICA or 1-alkenes can increase the solubility of lighter ones, and conversely lighter compounds can decrease the solubility of heavier ones (the so-called co-solubility effect). [2][3][4] Previous papers from our research group have discussed the impact of the solubility effect of a number of ICA for high density polyethylene (HDPE) on reaction rate, [5] the molecular weight distribution and particle morphology, [6] crystallization rate, [7] and reactor behavior. [8] On the other hand, very little experimental work has been done to understand the impact of adding ICA on ethylene…”
mentioning
confidence: 99%